Study of operating conditions for biodiesel production from sludge palm oil using chemical reactor - Hayyan, Adeeb; Alam, Md. Zahangir; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen; Mohd Hakimi, Noor Irma Nazashida; Mohd Siran, Yosri; Tahiruddin, Shawaluddin (2009)
The main challenges for biodiesel production are the cost of raw material (fats and oils) and the cost of processing. In oil palm industry there are large amounts of low grade oils that could be converted to biodiesel such as sludge palm oil (SPO). SPO is an attractive feedstock and a significant raw material for biodiesel production. The use of SPO can lower the cost of biodiesel production significantly. The biodiesel production from SPO involved both esterification and transesterification process. An acid catalyst was used in the pretreatment of SPO with the presence of alcohol to esterify the free fatty acids (FFA) and convert them into esters, followed by an alkali catalyst to transesterify the triglycerides. All experiments were performed in a 1.5 liter jacketed reactor. The results of the operating conditions for esterification process were: 2% wt/wt of sulfuric acid, molar ratio of methanol to oil 10:1 at 60o C. The yield of the final product was 71% with 0.1% FFA which meets the standard specifications for biodiesel quality.